KẾT QUẢ ÁP DỤNG PHƯƠNG PHÁP ĐO SÂU ĐIỆN PHỤC VỤ KHẢO SÁT ĐÁNH GIÁ NGUỒN NƯỚC NGẦM Ở KHU KINH TẾ - CẢNG HÒN LA TỈNH QUẢNG BÌNH - Tuyến, Đoàn Văn; Canh, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
Results of survey by electrical method for investigating groundwater resources in Hon La economic-shiping port area, Quang Binh province The investigation of groundwater resources and control of salt water intrusion from shore are urgent problems in coastal zone. In worldwide practice, combined geophysical methods had been used for solving some parts of these problems, in which electrical methods has some advantages to gather fast information not only about structural features of the environment, but also properties of ground water aquifer in favorable cases. This paper presents some surveyed results of electrical method to evaluate ground water conditions in Hon La economic – shiping port area, Quang Binh province - one typical example of ground water problem in semi-arid coastal zone of Vietnam. The 2-D resistivity technique of electrical surveys has revealed some fresh water bearing structures in fractured bedrocks. The results of a rational distribution of employed electrical measurements and combined interpretation of resistivity and hydrogeological data allow to determine the interfaces of fresh and salt water in both depth and surface in the area. The geoelectrical application is useful for initially evaluating environmental characteristics and potensiality of water resources in this area.